2018
DOI: 10.1016/j.bja.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Esketamine counters opioid-induced respiratory depression

Abstract: Esketamine effectively countered remifentanil-induced respiratory depression, an effect that was attributed to an increase in remifentanil-reduced ventilatory CO chemosensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 47 publications
2
100
0
Order By: Relevance
“…As we previously showed, breathing activity is initiated when remifentanil plasma concentrations drop to about 2 ng/ml. 15,16 We observed no differences in pain scores and morphine consumption in the PACU (table 3). This could be related to the inability of the nociception level to impact postoperative events when using short-acting opioids or to the use of preemptive morphine treatment.…”
Section: Secondary Endpointsmentioning
confidence: 75%
“…As we previously showed, breathing activity is initiated when remifentanil plasma concentrations drop to about 2 ng/ml. 15,16 We observed no differences in pain scores and morphine consumption in the PACU (table 3). This could be related to the inability of the nociception level to impact postoperative events when using short-acting opioids or to the use of preemptive morphine treatment.…”
Section: Secondary Endpointsmentioning
confidence: 75%
“…infusion of the NMDA receptor antagonist esketamine at a subanesthetic dose dose-dependently reversed respiratory depression induced by i.v. remifentanil 35 . This was underpinned by a stimulatory effect on ventilatory CO 2 chemosensitivity that was otherwise reduced by remifentanil alone 35 .…”
Section: Recent Advances In Countering Opioid-induced Respiratory Depmentioning
confidence: 99%
“…This was underpinned by a stimulatory effect on ventilatory CO 2 chemosensitivity that was otherwise reduced by remifentanil alone 35 . The esketamine effect had a rapid onset of action and it was driven by plasma pharmacokinetics 35 . By contrast, esketamine had little or no effect on resting ventilation.…”
Section: Recent Advances In Countering Opioid-induced Respiratory Depmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors should be considered when considering ketamine treatment. The second question has recently been addressed by Jonkman et al [64]. They showed that ketamine effectively counteracts opioid-induced respiratory depression, possibly through its (indirect) actions at the AMPA receptor [65].…”
Section: Expert Opinionmentioning
confidence: 99%